Genetic variation of maximal velocity and EMG activity - Missitzi, J.; Geladas, N.; Klissouras, V. (International Journal of Sports Medicine, 2008)
There is a scarcity of studies on genetic variation of essential components of neuromuscular performance, such as maximal velocity and EMG activity during maximal effort. Using the twin model and comparing intrapair differences between monozygotic (MZ) and dizygotic (DZ) twins, we derived for these neuromuscular components heritability estimates (h(2)), signifying the phenotypic variance due to genetic differences. A group of forty healthy male twins, 10 MZ and 10 DZ pairs, aged 21.5 +/- 2.4 and 21.0 +/- 2.1 yr, respectively, performed dynamic elbow flexion to assess maximal velocity, and maximal isometric contraction to assess EMG activity of the biceps brachii muscle. Intrapair differences for maximal velocity in MZ and DZ twins were 0.22 +/- 0.04 and 0.55 +/- 0.17 m.s(-1), and intrapair correlations were 0.95 and 0.54, respectively; h2 for maximal velocity was 0.84. Likewise, intrapair differences for EMG activity during maximal isometric contraction were 0.061 +/- 0.03 in MZ and 0.176 +/- 0.08 mV in DZ; the respective intrapair correlations were 0.93 and 0.46, and h(2) was 0.85. In conclusion, maximal velocity of the upper limb, using a simple movement of a single joint and EMG activity during maximal isometric contraction, seems to be highly heritable characteristics in humans.